10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
This study seeks to identify factors that are associated with whether older adults are homebound in rural and urban areas. Utilizing the 2022/23 National Health and Aging Trends Study data, we conducted bivariate analyses to compare homebound status among rural and urban residents. Additionally, we used logistic regression to identify socio-demographic correlates overall and stratified by rurality and key demographic characteristics. The results revealed that rural and urban older adults had similar rates of homebound status, but that the association between risk factors and being homebound differed by rurality. In particular, older age, poor health, and Medicaid status were all more strongly associated with being homebound among rural older adults than among their urban peers. Varying socio-demographic factors are associated with the risk of older adults becoming homebound across rural and urban settings. Policies to prevent and support homebound older adults should be tailored to geographic and individual characteristics.